Pengaruh Penerapan Green Accounting, Corporate Social Responsibility (CSR), Dan Kinerja Lingkungan Terhadap Kinerja Keuangan - Khairul Anam; Dade Nurdiniah (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
This study aims to analyze the effect of Green Accounting, Corporate Social Responsibility, and Environmental Performance on financial performance measured by Return on Assets (ROA) in companies listed on the Indonesia Stock Exchange during the 2019–2024 period. This study uses a quantitative approach with multiple linear regression analysis. The data were secondary data obtained from annual financial statements, sustainability reports, and PROPER environmental ratings. Purposive sampling was used to select 19 companies, resulting in a total of 114 observation data. Data analysis was conducted using IBM SPSS Statistics 27, including classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination (R²) tests. The results show that Corporate Social Responsibility has a positive and significant effect on Return on Assets (ROA), while Green Accounting and Environmental Performance do not have a significant direct effect. Simultaneously, Green Accounting, Corporate Social Responsibility, and Environmental Performance significantly influence financial performance, indicating that the integration of sustainability practices contributes to overall profitability. This study provides theoretical and practical insights for companies to improve financial performance by implementing effective sustainability strategies and integrating environmental, social, and financial management.